Effect of Artemisia vulgaris Extract on VEGF Expression, CD34, Microvascular Density, and Diameter of Mammary Adenocarcinoma Tumors: In vivo Study - Putri Endah Puspitaningtyas; Subiyakto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Breast cancer in Indonesia still has a high incidence. Surgery remains the main choice with other modalities such as chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). This study aimed to prove that administration of AV extract reduced VEGF expression, CD34 and microvascular density (MVD), and tumor diameter in mammary adenocarcinoma. Methods. This study used a "Posttest only control group design" design for 24 female C3H mice which were selected randomly and divided into four groups, namely: group K (control), P1 (chemotherapy), P2 (extract), and P3. (combination). Mammary adenocarcinoma was derived from the inoculation of donor mice. AC chemotherapy (Adriamycin 0.18 mg and Cyclophosphamide 1.8 mg) was given in 2 cycles. AV is given at a dose of 13 mg (0.2 ml) once a day orally. VEGF and CD34 expression were assessed by immunohistochemical staining whereas MVD was assessed by the hematoxylin-eosin stain. Tumor diameter was measured using tumor calipers. Results. There was a significant relationship between CD34 expression and tumor diameter (p<0.001; r=0.927). There was a significant relationship between CD34 expression and MVD features (p<0.001; r=0.906). There was a significant relationship between CD34 and VEGF expression (p<0.001; r=0.986). There was a significant relationship between tumor diameter and VEGF expression (p<0.001; r=0.903). There was a significant relationship between tumor diameter and the appearance of MVD (p<0.001; r=0.882). There was a significant relationship between VEGF expression and MVD features (p<0.001; r=0.893). Conclusion. AV extract gave a higher response to chemotherapy in mammary adenocarcinoma of C3H mice given AC. a chemotherapy regimen (p=<0.05).